Characterization and plasticity of wharton's jelly mesenchymal stem cells of goat - Neves, Gustavo Cardoso da Silva (2021)
Mesenchymal stem cells (MSCs), obtained from several anatomical sites, have already been described, characterized and used in therapeutic models for tissue repair. The umbilical cord mesenchymal stem cells, represented by cells from arteries and veins walls, as well as Wharton's jelly are easy to be obtained, highly available, require no invasive procedure, do not present risk to donors and do not present ethical limitation. The aim of this research was to analyze the plasticity of Wharton's jelly mesenchymal stem cells (WJ-MSCs) of goat, evaluating their behavior in vitro and characterizing them immunophenotypically. Thus, tests were performed on colony forming units, viability and cell growth curve, flow cytometry analysis and plasticity potential. Goat umbilical cord matrix cells exhibited fibroblastoid morphology with colony formation and self-renewal ability, always maintaining their undifferentiated state up to the eighth passage (P8). The growth curve kinetics exhibited the LAG, LOG, and DECAY phases, without displaying a PLATEAU phase. The plasticity assay demonstrated positive differentiation for osteogenic, adipogenic and chondrogenic lines, characterized by the synthesis of intracytoplasmic granules or extracellular matrix with the presence of calcium, lipids and proteoglycans. Flow cytometry demonstrated the expression of CD90 and CD105; absence of CD14 expression.  It is concluded that the cell population isolated from the Wharton's  jelly of goat constitutes a representative sample of mesenchymal stem cells, with great possibilities in the field of regenerative and reproductive medicine.